Treatment Patterns and Adverse Event-Related Hospitalization Among Patients with Epidermal Growth Factor Receptor (EGFR)-Mutated Metastatic Non-small Cell Lung Cancer After Treatment with EGFR Tyrosine Kinase Inhibitor and Platinum-Based Chemotherapy Regimens - Elizabeth Marrett; Winghan Jacqueline Kwong; Jipan Xie; Ameur M. Manceur; Selvam R. Sendhil; Eric Wu; Raluca Ionescu-Ittu; Janakiraman Subramanian (Adis, Springer Healthcare, 2023)
Abstract Background Epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR TKIs) are established first-line treatments among patients with metastatic non-small cell lung cancer harboring EGFR-sensitizing mutations. Upon EGFR TKI resistance, there are scant data supporting a standard of care in subsequent lines of therapy. Objective We aimed to characterize real-world treatment patterns and adverse events associated with hospitalization in later lines of therapy. Methods This retrospective analysis of administrative claims included adults with metastatic non-small cell lung cancer who initiated a next line of therapy (index line of therapy) following EGFR TKI and platinum-based chemotherapy discontinuation on/after 1 November, 2015. Treatment regimens and adverse event rates during the index line of therapy were described. Results Among 195 eligible patients (median age: 59 years; female: 60%), the five most common index line of therapy regimens were immune checkpoint inhibitor monotherapy (29%), EGFR TKI monotherapy (21%), platinum-based chemotherapy (19%), non-platinum-chemotherapy (13%), and EGFR TKI combinations (9%). The overall median (95% confidence interval) time to discontinuation of the index line of therapy was 2.8 (2.1-3.2) months. Common adverse events associated with hospitalizations included infection/sepsis, pneumonia/pneumonitis, and anemia (2.9, 2.8, and 2.0 per 100 person-months, respectively). Conclusions Among EGFR TKI-resistant patients who discontinued platinum-based chemotherapy, the duration of the next line of therapy was short, treatment was highly variable, and re-treatment with EGFR TKIs and platinum-based regimens was common, suggesting a lack of standard of care in later lines. Adverse event rates associated with hospitalization were high, especially among platinum-treated patients. These results underscore the unmet need for new therapies in a later line of treatment to reduce the clinical burden among patients in this population.